Small field output factors evaluation with a microDiamond detector over 30 Italian centers. Issue 12 (December 2016) - Russo, Serenella; Reggiori, Giacomo; Cagni, Elisabetta; Clemente, Stefania; Esposito, Marco; Falco, Maria Daniela; Fiandra, Christian; Giglioli, Francesca Romana; Marinelli, Marco; Marino, Carmelo; Masi, Laura; Pimpinella, Maria; et al.
Highlights: New generation detector PTW microDiamond was tested over 30 Italian centers. The study provide an OF dataset useful for the small field dosimetry standardization. A correct methodology is required to compare results for different centers. Abstract: Purpose: The aim of the study was a multicenter evaluation of MLC&jaws-defined small field output factors (OF) for different linear accelerator manufacturers and for different beam energies using the latest synthetic single crystal diamond detector commercially available. The feasibility of providing an experimental OF data set, useful for on-site measurements validation, was also evaluated. Methods: This work was performed in the framework of the Italian Association of Medical Physics (AIFM) SBRT working group. The project was subdivided in two phases: in the first phase each center measured OFs using their own routine detector for nominal field sizes ranging from 10 × 10 cm 2 to 0.6 × 0.6 cm 2 . In the second phase, the measurements were repeated in all centers using the PTW 60019 microDiamond detector. Results: The project enrolled 30 Italian centers. Micro-ion chambers and silicon diodes were used for OF measurements in 24 and 6 centers respectively. Gafchromic films and TLDs were used for very small field OFs in 3 and 1 centers. Regarding the measurements performed with the user's detectors, OF standard deviations (SD) for field sizes down to 2 × 2 cm 2 were in all cases <2.7%. In the second phase, a reduction of around 50% of the SD was obtained using the microDiamond detector. Conclusions: The measured values presented in this multicenter study provide a consistent dataset for OFs that could be a useful tool for improving dosimetric procedures in centers. The microDiamond data present a small variation among the centers confirming that this detector can contribute to improve overall accuracy in radiotherapy.